2022
DOI: 10.33084/jsm.v8i3.3161
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review: Efektifitas Metode Moist Wound Healing pada Ulkus Diabetik

Abstract: One of the complications of diabetes mellitus is the presence of ulcer wounds which cause 50% to 75% of amputation. This literature review aims to determine the effectiveness of the Moist Wound Healing method in diabetic wounds. The design of this scientific paper is a literature review search using an electronic database, namely google scholar, semantic scholar, and pubmed. The keywords used in the search were: diabetes mellitus AND moist AND diabetic ulcer. Based on a literature review of 4 articles, signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…From experience and research it is proven that behavior based on knowledge will last longer in a person's life than behavior that is not based on knowledge (15). Based on the definitions above, it can be concluded that knowledge is the result of the process of remembering and recognizing objects that have been studied through the five senses in a particular field properly (16).…”
Section: An Overview Of the Patient's Knowledge Level About Anesthesi...mentioning
confidence: 99%
“…From experience and research it is proven that behavior based on knowledge will last longer in a person's life than behavior that is not based on knowledge (15). Based on the definitions above, it can be concluded that knowledge is the result of the process of remembering and recognizing objects that have been studied through the five senses in a particular field properly (16).…”
Section: An Overview Of the Patient's Knowledge Level About Anesthesi...mentioning
confidence: 99%